Development of Student Worksheets to Improve the Ability of Mathematical Problem Posing - Harry Dwi Putra; Tatang Herman; Utari Sumarmo (Universitas Ahmad Dahlan, 2017)
Activities posing and solving a problem are important parts in mathematics, so the problem posing is an activity that was instrumental in mathematical thinking and become an important part in solving the problem. This type of research is research and development that aims to develop student worksheets through scientific approach with what if not strategy. The research method consists of stages: literature study, observation, interviews, development of student worksheets, assessment of two experts, and restricted trial to the eleventh grade students in SMAN 2 Cimahi, SMAN 3 Cimahi, and SMAN 4 Cimahi. Based on the findings, it was concluded that the student worksheets through scientific approach with what if not strategy load some activities including observing, questioning, trying, reasoning, and concluding. The activity of questioning using what if not strategy involves changing data, adding data, changing data with the same question, or changing question with the same data. The student worksheets also presented some contextual problems in accordance with the experience of students. After tested using worksheet, the improvement of student mathematical problem posing in the three schools was in moderate criteria.